Programming of postnatal phenotype caused by exposure of cultured embryos from Brahman cattle to colony-stimulating factor 2 and serum. (3rd June 2021) - Estrada-Cortés, Eliab; Jannaman, Elizabeth A; Block, Jeremy; Amaral, Thiago F; Hansen, Peter J
Abstract: Alterations in the environment of the preimplantation embryo can affect competence to establish pregnancy and phenotype of resultant calves. In this study, the bovine embryo produced in vitro was used to evaluate postnatal programming actions of the embryokine colony-stimulating factor 2 (CSF2 ) and serum, which is a common additive of culture media. Oocytes were collected by ovum pick up from Brahman donors and fertilized with semen from Brahman bulls. Embryos were randomly assigned to one of the three treatments: vehicle, CSF2 10 ng/mL, or 1% (v/v) serum. Treatments were added to the culture medium from day 5 to 7 after fertilization. Blastocysts were harvested on day 7 and transferred into crossbred recipients. Postnatal body growth and Longissimus dorsi muscle characteristics of the resultant calves were measured. The percent of cleaved embryos becoming blastocysts was increased by serum and, to a lesser extent, CSF2. Treatment did not affect survival after embryo transfer but gestation length was shortest for pregnancies established with serum-treated embryos. Treatment did not significantly affect postnatal body weight or growth. At 3 mo of age, CSF2 calves had lower fat content in the Longissimus dorsi muscle and less subcutaneous fat over the muscle than vehicle calves. There was a tendency for cross-sectional area of the muscle to be smaller for serum calves than vehicle calves. Results confirm the importance of the preimplantation period as a window to modulate postnatal phenotype of resultant calves. In particular, CSF2 exerted actions during the preimplantation period to program characteristics of accumulation of intramuscular and subcutaneous fat of resultant calves. The use of a low serum concentration in culture medium from day 5 to 7 of development can increase the yield of transferrable embryos without causing serious negative consequences for the offspring.